Analysing the Impact of Hotels Customer Relationship Management Strategies on Customers Satisfaction and Loyalty with Hotels of Bhopal ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2025)
Background: Customer Relationship Management (CRM) strategies have become critical tools for establishing strong client relationships, enhancing customer experience and ensuring repeat business. These methods are vital in the hotel industry, particularly in Bhopal, where the focus is on customer satisfaction and loyalty. Objective: The objective of this research is to examine the impact of CRM strategies on customer satisfaction and loyalty in Bhopal’s hotel sector. The study investigates how various CRM practices, including staff friendliness, personalized services and information on local attractions, influence customer behavior. Methodology: The present research was conducted in Bhopal City, the capital of Madhya Pradesh, focusing on star category hotels. Data was collected from travelers above 18 years of age who had visited these hotels, using a convenience sampling technique. Data was gathered through a structured questionnaire developed on Google Forms and circulated via social media and emails. The survey included questions on the impact of hotel CRM strategies on customer satisfaction and loyalty, using a five-point Likert Scale. Data analysis is done based on 140 responses. Data collection was carried out in July and August 2024 and descriptive analysis, including weighted mean and percentage methods, was used to interpret the results. Results: The study revealed that personalization of services, with the highest weighted mean of 3.53, is the most impactful CRM strategy on customer satisfaction, followed closely by staff friendliness and helpfulness (3.51) and responsiveness to requests (3.49). Meanwhile, strategies such as follow-up after stay (3.13) and loyalty program benefits (3.29) are less influential on customer satisfaction. Conclusion: In conclusion, both objectives highlight the crucial role of personalized CRM strategies in driving customer satisfaction and loyalty. Personalization of services, staff friendliness and responsive communication are key to enhancing satisfaction, while personalized communication, loyalty programs and attention to customer preferences significantly foster loyalty. While these strategies generally lead to greater customer retention, their impact varies among individuals, suggesting that hotels should continually refine their CRM practices to meet diverse customer needs.
Keywords: CRM strategies; hotel industry; customer satisfaction; customer loyalty; Bhopal